Tunable Bifunctional Activity of MnxCo3−xO4 Nanocrystals Decorated on Carbon Nanotubes for Oxygen Electrocatalysis. Issue 8 (18th April 2018) - Zhao, Tingting; Gadipelli, Srinivas; He, Guanjie; Ward, Matthew J.; Do, David; Zhang, Peng; Guo, Zhengxiao
Abstract: Invited for this month's cover is the group of Prof. Zhengxiao Guo at the University College London. The image illustrates an integrated manganese cobalt oxide/nitrogen‐doped multiwalled carbon nanotube hybrid (MnCo2 O4 @NCNT) catalyst for bifunctional oxygen reduction and evolution reactions (ORR/OER), out‐performing the commercial Pt/C and IrO2/C standards, with potential applications for the oxygen electrode in rechargeable metal–air batteries to power drones and electric vehicles. The Full Paper itself is available at10.1002/cssc.201800049 . Abstract : "The main challenge in our research is developing highly effective and stable bifunctional ORR and OER electrocatalysts…" This and more about the story behind the research that inspired the Cover image is presented in the Cover Profile. Read the full text of the corresponding research at10.1002/cssc.201800049 . View the Front Cover here:10.1002/cssc.201800755 .